Comparison of Safety, Efficacy, and Cost-Effectiveness of Miconazole 2% Versus Sertaconazole 2% in the Treatment of TineaCorporis: A Randomized Control Trial: Pharmaceutical Science-Pharmacy practice for Good Health Promotion - NarayanaGorontla; Kanala Somasekhar Reddy; Raj Kamal; Kartheek Reddy; Thireesha Tanveer; NeelimaGanzi (International Journal of Life Science and Pharma Research, 2022)
Tineacorporis is a dermatophytic infection of the body, which involves the keratin layer of the skin. These lesions are present as an annular plaque with an advancing border along with central clearing. Miconazole, a topical antifungal drug and has good efficacy, in anti dermatophyte. Sertaconazole is a highly selective inhibitor of fungal cytochrome P-450 sterol C-14 α-demethylation via the inhibition of the enzyme cytochrome P450 14α-demethylase.It is claimed to be superior to other old topical imidazoles in tineacorporis. .The present study was aimed to compare the safety, efficacy and cost-effectiveness of topical antifungals, where we have compared Miconazole and Sertaconazole 2% creams in the treatment of fungal infection caused by tineacorporis, by assessing the ADR’s and therapeutic outcomes, using comparative, unicentered, randomized, non-blinded trial with 2 parallel treatment arms of one-month duration. In this study 106 patients were randomly assigned into 2 groups of Miconazole 2% cream and Sertaconazole 2% with 54 and 52 patients in each group respectively. Measurement is carried out at baseline, 1st, 2nd and 3rd follow-up for desired effects like itching, erythema, pain and lesions, physician’s global assessment (PGA), safety and cost-effectiveness. The results showed that sertaconazole 2% cream is efficacious and superior to Miconazole 2% cream in the improvement of clinical parameters and PGA. At the end of the follow-up phase, both groups of drugs are effective and well-tolerated in patients with no recurrence of tineacorporis. Effectiveness of SSertaconazole is early and superior with minor side effects. However, Miconazole is cost effective and safe.